2021
DOI: 10.1002/ajpa.24374
|View full text |Cite
|
Sign up to set email alerts
|

Testing the reliability of CT scan‐based dental wear magnitude scoring

Abstract: Objectives Digital models are now frequently used in biological anthropology (bioanthropology) research. Despite several studies validating this type of research, none has examined if the assessment of dental wear magnitude based on Computerized Tomography (CT) scans is reliable. Thus, this study aims to fill this gap and assess if dental wear magnitude scoring based on CT scans provides results consistent with scoring based on direct observation of the physical specimens. Materials and Methods Dental wear mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(72 reference statements)
0
0
1
Order By: Relevance
“…Dental wear was scored by the same observer (RMG), preventing inter-observer error. Although not all teeth were observed multiple times, a previous study with a sub-sample (n = 412) of the one used in this study showed no scoring differences between repeated observations by the same observer 126 . Dental wear scores of paired first and second molars were plotted using the ggplot2 package of R 92 .…”
Section: Methodscontrasting
confidence: 49%
“…Dental wear was scored by the same observer (RMG), preventing inter-observer error. Although not all teeth were observed multiple times, a previous study with a sub-sample (n = 412) of the one used in this study showed no scoring differences between repeated observations by the same observer 126 . Dental wear scores of paired first and second molars were plotted using the ggplot2 package of R 92 .…”
Section: Methodscontrasting
confidence: 49%